¿Existe el Enigma de la Prima de Riesgo en el Mercado Bursátil Colombiano? 1993-2002 (2004)
In this study we search for evidence of the existence of the equity premium puzzle in the colombian stock market and to estimate the risk aversion of a representative investor in this market. This study covers the period December 1993 – January 2002. For that propose we used the asset pricing model with a representative agent based on two different utility functions: CRRA and habit formation. We conclude that different than of the reported evidence in several developed and developing markets, in the Colombian stock market there is no evidence of the puzzle. As it is expected from by the low volatility of consumption and the low covariance between this one and the returns from stocks, the risk aversion coefficient characteristic of an investor in this market is close to zero.